Xenon attenuated neonatal lipopolysaccharide exposure induced neuronal necroptosis and subsequently improved cognition in juvenile rats - Liao, Zhimin; Ou, Xiaofeng; Zhou, Cheng; Ma, Daqing; Zhao, Hailin; Huang, Han (Frontiers in Pharmacology, 2022)
Background: Neonatal sepsis is known to cause neurodevelopment impairment and has been reported to increase risks for neurological/psychiatric disorders. In this study, we investigated the effect of xenon, a well-known potent neuroprotective gas, on neonatal sepsis-induced neurodevelopment impairment in rats together with underlying mechanism by focusing on receptor-interacting protein kinase (RIP) mediated neuronal necroptosis. . Methods: 3-day-old Sprague–Dawley rat pups were exposed to either 70% xenon or N2 balanced with O2 for 6 hours, during which lipopolysaccharide (LPS) was injected intraperitoneally for 3 times (500 µg/kg for the 1st and 250 µg/kg for the 2nd and 3rd dose; n = 6-10 /group). In another cohort of 3-day-old rat pups, intracerebroventricular injection of necrostatin-1 (4 µg in 4 µl saline, a RIP-1-targeted inhibitor of necroptosis) was performed 20 min after the 3rd dose of LPS. The learning ability and memory were assessed 25 days after LPS injection. Then, their hippocampus was collected for neuronal necroptosis with RIP and MIKL assessments using western blot and in situ immunostaining. Systemic and neuro-inflammation was also assessed. Results: LPS insult resulted in elevation of pro-inflammatory cytokine TNF-𝝰 and IL-6, caused neuronal necroptosis and damaged synaptic integrity at the brain developing stage, which finally led to the long-term cognitive impairment. Xenon inhibited necroptosis associated mediator RIP-1, RIP-3 and MLKL activation, protected neurons and attenuated cognitive dysfunction induced by LPS. Like xenon, the similar pattern changes induced by a RIP-1 inhibitor Necrostatin-1 were also found. Conclusion: This study indicates that necroptosis is involved in neonatal sepsis-induced neurofunctional impairments and xenon may be a novel therapeutic strategy to prevent/treat cognitive impairment for neonatal septic patients.